Desarrollo de un sistema prototipo de control para mezclado y monitoreo del proceso de fumigación manual en plantaciones de cacao de la comuna Flor del Valle - Santo Domingo de los Tsáchilas - Molina Puma, Diego Armando (2016)
Through developing this project a prototype control system for the benefit in the process of manual spraying cocoa plantations Flower Valley Commune of the Province of Santo Domingo de los Tsáchilas implemented. This project will help small farmers in the area to achieve dose correctly, health care, minimize the risk for contamination with agrochemicals and waste there of which affect the environment and to their environment. This prototype control system has two parts: the first part integrates automatic mixing tank, which has a dosing system agrochemical control for water level, an agitator for mixing and transfer to the respective pump manually spraying. Inside its structure are major elements as: ultrasonic sensors, infrared sensors, DC motor, fluid transfer pump, lights for warnings, data display (LCD display), 12-volt battery and solenoid, making control the concentration of the chemical. The second part is the pump control manual spraying by monitoring temperature and relative humidity present in cocoa plantations are coupled main elements such as sensor temperature and relative humidity, lights for warnings, display data, 12 volt battery, and solenoid control for locking and unlocking operation of the sprayer when the environmental conditions are not suitable for fumigation.